Genetic and molecular mechanisms underlying the parthenocarpic fruit mutation in tomato - Picarella, Maurizio E.; Ruiu, Fabrizio; Selleri, Luigi; Presa, Silvia; Mizzotti, Chiara; Masiero, Simona; Colombo, Lucia; Soressi, Gian Piero; Granell, Antonio; Mazzucato, Andrea (Frontiers in Plant Science, 2024)
Parthenocarpy allows fruit set independently of fertilization. In parthenocarpic-prone tomato genotypes, fruit set can be achieved under pollen-limiting environmental conditions and in sterile mutants. Parthenocarpy is also regarded as a quality-related trait, when seedlessness is associated with positive fruit quality aspects. Among the different sources of genetic parthenocarpy described in tomato, the parthenocarpic fruit (pat) mutation is of particular interest because of its strong expressivity, high fruit set, and enhanced fruit quality. The complexity of the pat “syndrome” associates a strong competence for parthenocarpy with a complex floral phenotype involving stamen and ovule developmental aberrations. To understand the genetic basis of the phenotype, we mapped the pat locus within a 0.19-cM window of Chr3, comprising nine coding loci. A non-tolerated missense mutation found in the 14th exon of Solyc03g120910, the tomato ortholog of the Arabidopsis HD-Zip III transcription factor HB15 (SlHB15), cosegregated with the pat phenotype. The role of SlHB15 in tomato reproductive development was supported by its expression in developing ovules. The link between pat and SlHB15 was validated by complementation and knock out experiments by co-suppression and CRISPR/Cas9 approaches. Comparing the phenotypes of pat and those of Arabidopsis HB15 mutants, we argued that the gene plays similar functions in species with fleshy and dry fruits, supporting a conserved mechanism of fruit set regulation in plants.